Fertilidade do solo, composição mineral e produção do quiabeiro sob lâminas de irrigação e matéria orgânica - Bertino, Antonio Michael Pereira (2018)
The okra is a vegetable that has been gaining expression in the Northeast region, but the information on irrigation management and organic fertilization is still infrequent in the literature, therefore, research in this sense must be developed. In this direction an experiment was developed to evaluate the productive performance of the okra and the chemical attributes of the soil as a function of irrigation slides and soil organic matter, was developed in the field in a Neossolo Flúvico with the cultivar santa cruz 47. The experimental design was a randomized complete block design in a 2 x 5 factorial scheme, with 100 % and 50 % of crop evapotranspiration (ETc) irrigation and five doses of bovine manure to raise soil organic matter content from 18 to 28, 38, 48 and 58 g dm-3 in the productive cycles of 2013/2014 and 2014/2015. The variables studied were the components of soil fertility, contents foliar macronutrients and okra components. Irrigation with the 100 % ETc blade increased soil fertility when compared to the 50 % ETc blade. The soil organic matter increased the fertility potential expressed by OM, P, K, Ca, Mg, S resulting in increased cation exchange capacity, foliar contents of P, K and Mg and in the components of okra production. Greater productivity was obtained with 48 g dm-3 of bovine manure. It is recommended the application of OMS through bovine manure, at the dose of 48 g dm-3.